A Preventative Guidance Program To Reduce Cardiac Arrest Risk In Sports Competitions - Ammar Yasser Katouf (Journal of Education and Sport Science, 2026)
Objectives: This study aimed to develop a preventive guidance program to reduce the risk of cardiac arrest among football players during sports competitions in Iraq. It also examined the extent to which sports clubs provide health services and the level of players’ health awareness related to cardiac arrest prevention and first aid. Materials and Methods: A descriptive survey design was employed. The study was conducted in Iraqi first-division football clubs during the 2023 season. The main sample consisted of 660 participants, including 60 medical staff members and 600 players. Two structured questionnaires were used: one assessed club-based health services, including medical examination, health education, and health support, while the other assessed players’ health awareness regarding heart protection and first aid for cardiac arrest. The validity and reliability of the instruments were verified using internal consistency and Cronbach’s alpha. Data were analyzed using percentages, arithmetic means, chi-square tests, correlation coefficients, and Cronbach’s alpha. Results: The findings showed weaknesses in the medical examination procedures, health education activities, and health support provided by sports clubs to protect players from cardiac arrest. The results also indicated that players had limited health awareness regarding heart protection, regular medical check-ups, nutrition, recovery practices, and cardiopulmonary resuscitation. Based on these findings, a preventive guidance program was developed around four main pillars: regular cardiovascular medical check-ups, nutrition and supplementation for heart health, sleep and recovery practices, and first aid and CPR awareness. Conclusions: The study concluded that Iraqi football clubs need stronger preventive health procedures to reduce cardiac arrest risk among players. The proposed preventive guidance program may serve as a practical framework for improving medical monitoring, player education, and emergency preparedness in sports clubs.